1999
DOI: 10.1093/emboj/18.3.522
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde Ca2+ signaling in C2C12 skeletal myocytes in response to mitochondrial genetic and metabolic stress: a novel mode of inter-organelle crosstalk

Abstract: We have investigated the mechanism of mitochondrialnuclear crosstalk during cellular stress in mouse C2C12 myocytes. For this purpose, we used cells with reduced mitochondrial DNA (mtDNA) contents by ethidium bromide treatment or myocytes treated with known mitochondrial metabolic inhibitors, including carbonyl cyanide m-chlorophenylhydrazone (CCCP), antimycin, valinomycin and azide. Both genetic and metabolic stresses similarly affected mitochondrial membrane potential (Δψ m ) and electron transport-coupled A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
416
1
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 345 publications
(447 citation statements)
references
References 78 publications
29
416
1
1
Order By: Relevance
“…This change in Dc m was accompanied by elevated cytosolic free [Ca 2+ ] c and activation of calcium responsive transcription factors (Biswas et al, 1999). Our results also demonstrated that the mitochondria-to-nucleus stress signaling induces invasive phenotypes in otherwise non-invasive C2C12 rhabdomyoblasts (Amuthan et al, 2001).…”
Section: Introductionsupporting
confidence: 67%
See 3 more Smart Citations
“…This change in Dc m was accompanied by elevated cytosolic free [Ca 2+ ] c and activation of calcium responsive transcription factors (Biswas et al, 1999). Our results also demonstrated that the mitochondria-to-nucleus stress signaling induces invasive phenotypes in otherwise non-invasive C2C12 rhabdomyoblasts (Amuthan et al, 2001).…”
Section: Introductionsupporting
confidence: 67%
“…This change in Dc m was accompanied by elevated cytosolic free [Ca 2+ ] c and activation of calcium responsive transcription factors (Biswas et al, 1999). Our results also demonstrated that the mitochondria-to-nucleus stress signaling induces invasive phenotypes in otherwise non-invasive Tumor-specific markers cathepsin L and transforming growth factor b1 (TGFb1) were shown to be among the several genes that are overexpressed in cells subjected to mitochondrial genetic and metabolic stress.…”
Section: Introductionsupporting
confidence: 59%
See 2 more Smart Citations
“…In animal cells, for example, compromises in mitochondrial function or certain external cues can lead to increased expression of genes encoding components of the mitochondrial oxidative phosphorylation apparatus and, in some instances, lead to a general increase in the biogenesis of mitochondria (Lunardi and Attardi, 1991;Scarpulla, 1997;Biswas et al, 1999;Heddi et al, 1999;Murdock et al, 1999;Wu et al, 1999;Amuthan et al, 2001). These events are controlled, in part, by transcriptional activators and coactivators whose targets include nuclear genes encoding mitochondrial proteins.…”
Section: Introductionmentioning
confidence: 99%